The Application of Microlearning for Employee Upskilling - Mochammad Syafana Hilmy Khodir; Beny Mahyudi Saputra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to explore in depth the perceptions and experiences of employees in applying microlearning for upskilling complex skills. In this era of disruption, upskilling has become crucial, and microlearning has been widely adopted due to its flexibility. However, its effectiveness for deep competencies (not just procedural knowledge) is still not qualitatively understood. Using a qualitative case study design in a technology organization, data were collected through 17 semi-structured in-depth interviews with employees, managers, and the L&D team, then analyzed thematically. The results reveal three key findings. First, there is a dualistic perception: microlearning is praised as a just-in-time (JIT) tool, but is perceived as "superficial" for soft skills. Second, employees bear a heavy cognitive "synthesis burden" due to content fragmentation, forcing them to "stitch together" pieces of information themselves. Third, success is highly dependent on contextual factors, particularly proactive manager support and the availability of social learning interactions.